2014
DOI: 10.1371/journal.pone.0108263
|View full text |Cite
|
Sign up to set email alerts
|

Hyperandrogenemia in Polycystic Ovary Syndrome: Exploration of the Role of Free Testosterone and Androstenedione in Metabolic Phenotype

Abstract: ObjectiveTo evaluate the association between androstenedione, testosterone, and free testosterone and metabolic disturbances in polycystic ovary syndrome.MethodsWe analyzed the association between androstenedione, testosterone, and free testosterone and metabolic parameters in a cross-sectional study including 706 polycystic ovary syndrome and 140 BMI-matched healthy women. Polycystic ovary syndrome women were categorized into 4 groups: normal androstenedione and normal free testosterone (NA/NFT), elevated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 40 publications
(51 reference statements)
8
63
0
4
Order By: Relevance
“…In fact, it is well know that insulin excess is able to stimulate theca cell steroidogenesis and reduces hepatic SHBG synthesis, thereby leading to hyperandrogenemia (8). This has been confirmed by a long list of studies showing a significant association between insulin and androgens, particularly testosterone and androstenedione (13,14,18). In addition, there is a general consensus that in most women with PCOS, a mild-tomoderate insulin resistance may be responsible for the high prevalence of the metabolic syndrome (39) and that insulin sensitizers, such as metformin, may improve total and free testosterone in these women (1,8).…”
Section: Severe Insulin-resistant Syndrome and Pcosmentioning
confidence: 91%
See 2 more Smart Citations
“…In fact, it is well know that insulin excess is able to stimulate theca cell steroidogenesis and reduces hepatic SHBG synthesis, thereby leading to hyperandrogenemia (8). This has been confirmed by a long list of studies showing a significant association between insulin and androgens, particularly testosterone and androstenedione (13,14,18). In addition, there is a general consensus that in most women with PCOS, a mild-tomoderate insulin resistance may be responsible for the high prevalence of the metabolic syndrome (39) and that insulin sensitizers, such as metformin, may improve total and free testosterone in these women (1,8).…”
Section: Severe Insulin-resistant Syndrome and Pcosmentioning
confidence: 91%
“…In fact, increasing evidence supports that androgen excess represents a constitutive biomarker of PCOS. As expected, an androgen profile rather than testosterone alone should be used, as documented by several recent studies (12,13,14,15,16,18). A fundamental prerequisite is represented by the fact that if different androgens are needed to fully define hyperandrogenemia in these women, it could be that different mechanisms may be involved in regulating the enzyme activity involved in the androgen production rate or in their metabolic clearance rate (18).…”
Section: Arguments In Favor Of the Definition Of Secondary Pcosmentioning
confidence: 96%
See 1 more Smart Citation
“…They also reported a strong negative association between serum androstenedione and insulin sensitivity, and a high incidence of glucose intolerance correlating with the severity of the androgen phenotype. Interestingly, Lerchbaum et al (76) reported that elevated free testosterone, unlike isolated androstenedione elevation, was associated with an adverse metabolic phenotype.…”
Section: Alternative Approach: Measuring Androstenedionementioning
confidence: 99%
“…The combination of total testosterone, androstenedione and free testosterone provides good accuracy for diagnosis of PCOS and its hyperandrogenemic sub-phenotypes (76,77,78). However, application for predicting metabolic risk in PCOS needs further investigation (79).…”
Section: Alternative Approach: Measuring Androstenedionementioning
confidence: 99%